2012
DOI: 10.4161/onci.18852
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of current approaches to inhibit regulatory T cells in cancer

Abstract: CD4+CD25+Foxp3+ regulatory T cells (Treg) have emerged as a dominant T cell population inhibiting anti-tumor effector T cells. Initial strategies used for Treg-depletion (cyclophosphamide, anti-CD25 mAb…) also targeted activated T cells, as they share many phenotypic markers. Current, ameliorated approaches to inhibit Treg aim to either block their function or their migration to lymph nodes and the tumor microenvironment. Various drugs originally developed for other therapeutic indications (anti-angiogenic mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 78 publications
0
75
0
2
Order By: Relevance
“…The plasticity of regulatory T cells, transient expression of Foxp3 by activated T cells and a possible role of regulatory T cells in the inhibition of deleterious cancer inflammation could explain the paradoxically good clinical prognosis associated with regulatory T cells in some circumstances (43,44). Several hypotheses can also be proposed to explain this paradoxical favorable outcome associated with PD-1 expression on T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasticity of regulatory T cells, transient expression of Foxp3 by activated T cells and a possible role of regulatory T cells in the inhibition of deleterious cancer inflammation could explain the paradoxically good clinical prognosis associated with regulatory T cells in some circumstances (43,44). Several hypotheses can also be proposed to explain this paradoxical favorable outcome associated with PD-1 expression on T cells.…”
Section: Discussionmentioning
confidence: 99%
“…They were obtained from PolyPeptide Laboratories (Strasbourg, France), reconstituted in PBS and stored at À20 C. The STxB-E7 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] vaccine was produced by chemical coupling between the N-bromoacetylated E7 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] peptide and the sulfhydryl group of STxB-Cys recombinant protein, as previously described (23). After purification, endotoxin concentrations determined by the Limulus assay test (Lonza) were less than 0.5 EU/mg.…”
Section: Cellsmentioning
confidence: 99%
“…These results suggest that the rapalogs-induced T regs abrogate antitumor T-cell functions in vivo. Accordingly, we evaluated in vivo the combination of rapalogs with therapeutic agents that deplete T regs or block their suppressive functions (29). First, we showed that the anti-CD25 mAb (clone PC61.5; ref.…”
Section: The Presence Of T Regs In Vivo Altered the Efficacy Of Rapalmentioning
confidence: 99%
“…245 In this patient cohort, daclizumab provoked a decline in the circulating levels of CD4 C CD25 C FOXP3 C regulatory T cells 246 that correlated with the elicitation of humoral EGFR-specific immune responses.…”
Section: Gm-csf-adjuvanted Standalone Interventions In Subjects Bearimentioning
confidence: 99%